The Wartville Wizard - Madden, Don, 1927- (New York : Aladdin Paperbacks, 1993)
An old man fights a town of litterbugs by magically sending each piece of trash back to the person who dropped it.
School Library Journal.
School Library Journal, April 2008.
4.1.
4.1
K-3
Keywords: Environmental protection -- Juvenile fiction; Magic -- Juvenile fiction; Refuse and refuse disposal -- Juvenile fiction; Environmental protection -- Fiction; Magic -- Fiction; Refuse and refuse disposal -- Fiction; Environmental protection -- Fiction; Magic -- Fiction; Refuse and refuse disposal -- Fiction; Picture books for children